2011
DOI: 10.1007/s10722-011-9782-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of India hybrid tea

Abstract: IMPF: 01.55The most important evolutionary event in the success of commercial tea cultivation outside China in ca. 30 countries came about by the origin of India hybrid tea in India, derived from the extensive spontaneous hybridization that took place between the Assam type tea growing in the forest regions of Assam, North-East India and China type tea introduced from China in ~1875 to many regions of North-East India. The release of an enormous pool of vigorous and highly variable plants of India hybrid tea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…To date, two core collections of tea had been reported (Wang et al 2011;Raina et al 2012). The Chinese core collection of Wang et al (2011) was selected by using phenotypic data.…”
Section: Genetic Diversity and Population Structure Of Tea Germplasm mentioning
confidence: 99%
See 3 more Smart Citations
“…To date, two core collections of tea had been reported (Wang et al 2011;Raina et al 2012). The Chinese core collection of Wang et al (2011) was selected by using phenotypic data.…”
Section: Genetic Diversity and Population Structure Of Tea Germplasm mentioning
confidence: 99%
“…assamica from multiple countries have revealed that collections from China and India have high levels of genetic diversity, but these studies analyzed only a few dozen accessions (Wachira et al 2001;Matsumoto 2002, 2003;Yao et al 2008). More recently, some studies analyzed several hundred germplasms using simple sequence repeat (SSR) or amplified fragment-length polymorphism (AFLP) markers (Ohsako et al 2008;Yao et al 2012;Raina et al 2012;Fang et al 2012), but only domestic germplasms in Japan, China, or India.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Present SSR analysis revealed that China/China hybrids and Assam accessions shared 22 % average GS. Recently, AFLP based fingerprinting of 1644 tea accessions with large number of intergrades also revealed the high level of heterozygosity in Indian tea (Raina et al, 2011). …”
Section: (Tugms12)mentioning
confidence: 99%